Epstein-Barr virus reactivation and upper-respiratory illness in elite swimmers - Gleeson, M.; Pyne, D. B.; Austin, J.; Lynn Francis, J.; Clancy, R. L.; McDonald, W. A.; Fricker, P. A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of this study was to investigate the relationships between latent viral shedding of Epstein-Barr virus (EBV) in saliva, upper-respiratory illness, and mucosal immune suppression in a cohort of highly trained swimmers undertaking intensive training. METHODS: Saliva was collected before selected training sessions from 14 elite male swimmers during a 30-d period of intensive training. Prior infection with EBV was determined by EBV antibody serology. Salivary IgA concentrations were measured by enzyme linked immunosorbent assay (ELISA), and EBV viral shedding (EBV-DNA) was detected by polymerase chain reaction (PCR). Symptoms of upper-respiratory illness were recorded daily. RESULTS: Eleven swimmers (79%) were seropositive for prior EBV infection. Seven EBV seropositive swimmers (64%) had EBV-DNA detected during the study period. Upper-respiratory symptoms (URS) were reported in six of seven swimmers in whom EBV-DNA was detected and in three of four swimmers with no EBV-DNA detection. No URS were reported in the EBV seronegative swimmers. There was a statistically significant relationship between EBV serology status and URS (P = 0.027). EBV-DNA was detected in saliva before the appearance of URS. Salivary IgA levels were significantly lower immediately before the URS (P = 0.01) compared with subsequent peak IgA levels and declined to pre-URS levels on average 11 d after the first appearance of URS. CONCLUSIONS: The time course of appearance of EBV-DNA in relation to URS suggests latent viral EBV shedding may be a contributing factor in the URS. The low levels of salivary IgA detected before the URS indicated transient mucosal immune suppression in the study cohort. The viral shedding may alternatively be a reflection of the altered immune control mechanisms that occur in response to intensive exercise and unrelated to the URS.